Maternal and neonatal outcomes of congenital syphilis at a tertiary care center in Turkey; a retrospective observational study - Hasan Berkan Sayal; And Yavuz; Busra Tsakir; Erzat Toprak; Orkun Han; Hasan Ali Inal (Taylor & Francis Group, 2024)
Background Maternal syphilis (MS) can lead to significant maternal morbidity and neonatal morbidity and mortality if inadequately treated. This study is aimed to retrospectively analyse the maternal and neonatal outcomes of pregnant women diagnosed with MS at our clinic.Materials and Methods We accessed the medical records of 64 cases diagnosed with MS between 2020 and 2022 from our hospital database and the perinatology clinic archives in this retrospective observational study. Case distributions by years, sociodemographic characteristics, and maternal and neonatal outcomes were recorded.Results The distribution of MS cases was 16 (25.0%) in 2020, 20 (31.25%) in 2021, and 28 (43.75%) in 2022. The mean age of the patients was 26.4 ± 6.3 years, mean BMI was 23.36 ± 3.14, the smoking rate was 31.25%, and the majority of patients were educated to primary level (37.5%). Most were housewives (43.75%), lived in urban areas (43.75%), and had lower-level incomes (68.75%). In addition, 43.75% received adequate maternal treatment, the caesarean delivery rate was 43.25%, 31.25% had preterm births, and the mean birth weight was 2956.36 + 514.46 g. CS was largely diagnosed during delivery or the postpartum period (43.75%). Fifty percent of patients were in the latent stage, gestational hypertension and preeclampsia were present in four case each (6.25%), and gestational diabetes mellitus in eight (12.5%). Twenty babies (31.25%) were admitted to the neonatal intensive care unit, eight (12.5%) had congenital anomalies, 12 had foetal growth restriction (18.25%), stillbirth was present in four (6.25%) case, and early neonatal death in four (6.25%).Conclusions Delayed diagnosis and inadequate treatment of MS can lead to significant maternal and neonatal morbidity and mortality. Well-planned antenatal care services should be provided for all expectant mothers in order to reduce these adverse outcomes.